DNA barcoding and phylogenetic reconstruction of shark species landed in Muncar fisheries landing site in comparison with Southern Java fishing port - PREHADI PREHADI; ANDRIANUS SEMBIRING; EKA MAYA KURNIASIH; RAHMAD RAHMAD; DONDY ARAFAT; BEGINER SUBHAN; HAWIS H. MADDUPPA (Society for Indonesian Biodiversity, 2015)
Prehadi, Sembiring A, Kurniasih EM, Arafat D, Subhan B, Madduppa HH. 2015. DNA barcoding and phylogeneticreconstruction of shark species landed in Muncar fisheries landing site in comparison with Southern Java fishing port. Biodiversitas 16:55-61. Sharks are one of main fisheries commodity that are currently exploited on a large scale because of their high economic value.The identification of sharks has been a difficult one due to the specimen’s similarity in morphology and mostly have had key diagnosticfeatures removed. This study aimed to identify and to review the status of sharks, and also to reconstruct the shark species that werelanded at South Java fishing port using molecular approaches. The DNA amplification was using cytochrome oxidase I mitochondrial oflocus and 600-700 basepairs. A total of seven species from 59 individuals was identified including Alopias pelagicus, Carcharhinusfalciformis, C. sorrah, C. amblyrhynchos, Galeocerdo cuvier, Atelomycterus marmoratus, and Spyrna lewini. The diversity of sharkspecies landed in Muncar during the last 2 years has been decreased. The identified sharks species in this study sites were about 18% ofall Indonesian sharks. The result of this study is expected help the Government to manage shark fisheries in Indonesia.